Prototipe Tempat Sampah Cerdas Pemilah Sampah Organik Anorganik dan Pemantau Ketinggian Sampah Berbasis Android - Prawiroredjo, Kiki; Salma, Annisa (Jetri : Jurnal Ilmiah Teknik Elektro, 2024)
Big city like Jakarta produce large volumes of waste so that it becomes a problem for their dumps. If waste is sorted according to its type, it can be recycled to produce a useful product that can reduce the burden on landfills. Waste sorting can be done in households and in public places. Many public places have provided trash cans to facilitate sorting,  organic, inorganic, and metal waste. However, many people ignore garbage disposal bin that are suitable for their type. In public places where many people gather,  the trash can fill up quickly so that if the garbage picker has not thrown it away, the garbage can accumulate and overflow out. A system is needed that can sort of waste disposal according to its type so that the waste recycling process becomes efficient and a waste disposal system that implements information technology to overcome the accumulation of waste quickly. The system proposed in this study can sort the type of organic or inorganic waste and also make it easier for garbage pickers to know when to pick up garbage through a notification from a smartphone. To find out the type, the garbage was scanned using proximity sensors and infrared sensors. The trash can will open according to the type of garbage detected. The ultrasonic sensor measures the height of the garbage connected to the NodeMCU microcontroller as a data processor. Waste height data is sent through the internet network and displayed on the Blynk application. Based on the test results, the system has succeeded in distinguishing three types of waste, namely organic, inorganic, and metal waste. Based on the results of the garbage height test, it is known that the system has successfully provided a notification on the Blynk application if the garbage can is filled to 80% high.